MS4A2-rs573790 Is Associated With Aspirin-Exacerbated Respiratory Disease: Replicative Study Using a Candidate Gene Strategy - Pavón-Romero, Gandhi F.; Pérez-Rubio, Gloria; Ramírez-Jiménez, Fernando; Ambrocio-Ortiz, Enrique; Bañuelos-Ortiz, Elisé; Alvarado-Franco, Norma; Xochipa-Ruiz, Karen E.; Hernández-Juárez, Elizabeth; Flores-García, Beatriz A.; Camarena, Ángel E.; Terán, Luis M.; Falfán-Valencia, Ramcés (Frontiers in Genetics, 2018)
Aspirin-exacerbated respiratory disease (AERD) is a set of diseases of the unified airway, and its physiopathology is related to disruption of the metabolism of arachidonic acid (AA). Genetic association studies in AERD had explored single nucleotide polymorphism (SNPs) in several genes related to many mechanisms (AA metabolism, inflammation, drug metabolism, etc.) but most lack validation stages in second populations. Our aim is to evaluated whether contribution to susceptibility of SNPs reported in other populations are associated with AERD in Mexican Mestizo patients. We developed a replicative study in two stages. In the first, 381 SNPs selected by fine mapping of associated genes, (previously reported in the literature), were integrated into a microarray and tested in three groups (AERD, asthma and healthy controls -HC-) using the GoldenGate array. Results associated to risk based on genetic models [comparing: AERD vs. HC (comparison 1, C1), AERD vs. asthma (C2), and asthma vs. HC (C3)] were validated in the second stage in other population groups using qPCR. In the first stage, we identified 11 SNPs associated with risk in C1.The top SNPs were ACE-rs4309C (p=0.0001) and MS4A2-rs573790C (p=0.0002). In C2, we detected 14 SNPs, including ACE-rs4309C (p=0.0001). In C3, we found MS4A2-rs573790C (p=0.001). Using genetic models, C1 MS4A2-rs57370 CC (p=0.001) and ACE-rs4309 CC (p=0.002) had associations. In C2 ACE-rs4309 CC (p=0.0001) and C3 MS4A2-rs573790 CC (p=0.001) were also associate with risk. In the second stage, only MS4A2-rs573790 CC had significance in C1 and C3 (p=0.008 and p=0.03). We concluded that rs573790 in the MS4A2 gene is the only SNP that supports an association with AERD in Mexican Mestizo patients in both stages of the study.